Analysis Of Customer Decisions On Griya Hasanah Financing At Bank Syariah Indonesia Kcp Serang A Yani - Azahra, Afifah (Bina Bangsa International Journal of Business and Management, 2024)
This study aims to determine the influence of griya hasanah financing on customer decisions at islamic banks in Indonesia kcp serang a yani, service and quality in Indonesian Islamic banks are very wary in customer decisions so that customers are interested in taking griya hasanah financing at Indonesian Islamic banks. The The method used in this study is a qualitative method of the results of interviews and questionnaires. Data from this study was collected from internal documents of Bank Syariah Indonesia and the results of interviews of employees of Bank Syariah Indonesia KCP Serang A Yani. The answers of the average respondent from these four factors are influencing customer decisions in making Griya Hasanah financing. that age, religion, marital status and monthly income are very influential in customer decision making.in addition, the factors of products and services in Islamic banks are very influential in people's decisions in choosing Griya Hasanah financing. The bigger the company acts proactively, improves the service the better, then multiplies promotions that attract more customers, and can retain customers who have joined newer strategies so that customers are more interested.